Pryloysis of Coffee Husks for Biochar Production - Kiggundu, Nicholas; Sittamukyoto, Julius (Journal of Environmental Protection, 2019)
Effective utilization of coffee wastes has been a great challenge in Uganda despite their wider use to replenish soil organic matter. This study explored the possibility of producing biochar from coffee husks that could be used as a soil amendment for replenishing soil nutrients and also for enhancement of soil water holding capacity. Pyrolysis of coffee husks was done in a batch bio-reactor under slow pyrolysis conditions of temperatures 350˚C - 550˚C and residence times 30 - 60 min. For easy characterization, biochar was grinded, sieved through a 1 mm sieve and then analyzed using a computerized Thermo Graphic Analyzer with an inbuilt and integrated ELTRA 84 GmbH Precision Digital weighing scale. Proximate analysis (wet basis) of biochar gave a moisture content of 5.2%, ash content of 14.7%, volatile matter of 13.2% and fixed carbon of 66.9%. Biochar was applied to soil at different rates (0%, 5%, 10% and 20% w/w) and its effect on water holding capacity was investigated. Results show that biochar amended soils had higher water holding capacity (p ≤ 0.05) compared to biochar free soils. The water holding capacity also increased with increase in biochar amendment with a 1.5% increase in soil water holding capacity for each 1% increase in biochar application rate. Biochar was also rich in soil nutrient elements with 0.96% N, 0.39% P and 1.97% K; this increased the availability of soil nutrients for crop growth. The results suggest that biochar could be a better tool to improve soil conditions thus enhancing the sustainability of agriculture.
Keywords: Coffee Husks; pryloysis; Biochar; Soil Organic Matter; Soil Nutrients